Analisis Potensi Debit Air Tanah Melalui Pumping Test Metode Step Draw Down pada Sumur Bor Irigasi di Desa Bonto Rannu, Kecamatan Kajang, Kabupaten Bulukumba, Sulawesi Selatan - Agussalim; Muliana Djafar; Andi Syam Rizal (JFT : Jurnal Fisika dan Terapannya, 2022)
The rice fields in Bonto Rannu Village, Kajang District, Bulukumba Regency are dominated by rainfed rice fields. This species has limitations in the dry season because irrigation/agricultural irrigation is completely dependent on rainwater. Therefore, it is necessary to identify alternative irrigation sources for the sustainability of farmers' farming activities in Bonto Rannu Village. This study aims to analyze the quantity of groundwater wells by testing in the form of a pump test (pumping test) with the step draw down method. The optimum discharge (Qopt) of well 1 is 0.01876 m3/s or 67.53 m3/hour with an optimum Sw of 2.891 m. This shows that groundwater in well 1 can be pumped at 67.53 m3/hour with a decrease in water level of 2.891 m with the pump condition still technically safe. As for well 2, the optimum discharge (Qopt) is 0.00318 m3/s or 11.45 m3/hour with an optimum Sw of 2.100 m. These data indicate that there are limited groundwater reserves.